GW24-e3131 Evaluation of left ventricular diastolic synchronism in patients with hypertrophic cardiomyopathy by two dimensional speckle tracking imaging. (1st October 2013) - Xinqiao, Tian; Min, Liu; Hongyan, Cao; Shengjun, Tuo; Lei, Zuo; Liping, Yang; Juan, Zhou; Ao, Ru; Liwen, Liu
Abstract : Objectives: To evaluate diastole synchrony of the different segments of left ventricular in patients with hypertrophic cardiomyopathy by two dimensional speckle tracking imaging. Methods: Forty-seven patients with HCM and thirty-three healthy volunteers were studied by two dimensional speckle tracking imaging. Two-dimensional echocardiography was performed to collect three consecutive cardiac cycles dynamic images of left ventricular four-chamber view, two chamber view, apical long axis view and parasternal short axis mitral view, papillary view. The peak time of early and late diastolic longitudinal, radial, circumferential strain rate (TESRL, TASRL, TESRR, TASRR, TESRC and TASRC ) were measured from the start point of QRS wave of electrocardiogram. The left ventricular segmental standard deviation (SD-TESRL, SD-TASRL, SD-TESRR, SD-TASRR, SD-TESRC and SD-TASRC ) were calculated, which were served as diastolic synchronism indexes in assessing LV diastolic aspect. Results: SD-TESRL, SD-TASRL, SD-TESRR, and SD-TESRC were significantly longer in patients with HCM than in normal controls. SD-TASRR and SD-TASRC were longer in patients with HCM than in normal controls, but the difference had no statistical significance. Conclusions: Left ventricular diastole dyssynchrony can be evaluated accurately in patients with hypertrophic cardiomyopathy by two dimensional speckle tracking imaging.